AQUASCAPE MENENANGKAN PIKIRAN DAN MELATIH KREATIVITAS SISWA SMA, KECAMATAN WIYUNG KOTA SURABAYA - Ummul Firmani; Zulfaa Unzila Azizi; Saidah Luthfiyah (Universitas Muhammadiyah Gresik, 2020)
Wiyung Subdistrict is part of Surabaya City, once an agricultural area, but now all agricultural land has been developed into a densely populated residential area and shops. The livelihoods of most residents are traders, builders, factory workers, laborers, private employees and teachers. Wiyung which is part of Surabaya City, the second largest Metropolis City in Indonesia, feels the impact of the development of the city. The bad impact is the high pollution both air, soil and water. Air pollution comes from high smoke from motor vehicles and factories. This causes a lack of access to clean and healthy oxygen and a comfortable and beautiful place to stay free from pollution. For this reason, this community service program is implemented with the aim of providing education about a healthy and beautiful environment to residents, especially school age children. School-age children were chosen because they have great opportunities to develop and there are wide open opportunities to hone their skills to create beautiful environments through aquascape design training. Short-term goal is that they have the skills to make Aquascape to add beautiful and comfortable places to live and as a contributor to oxygen in the home environment. The long term goal is that they will be able to develop their business from the hobby of making Aquascape. The target participants of this program are high school students who live in Putri ‘Aisyiyah Orphanage, Wiyung District. At the Orphanage, children do not have activities to fill free time, so this service program is appropriate if it is there. Aquascape making activities are part of fish and plant cultivation activities. From the results of questionnaire questionnaires and direct interviews with the children and caretakers of the institution it was concluded that they were very enthusiastic about aquascape training because it was a new knowledge and experience for them.